PENGEMBANGAN RELIGIUSITAS ANAK USIA 5-6 TAHUN DI TAMAN PENDIDIKAN AL-QUR’AN (TPQ) HADIQOTUL AFHAM DUSUN PERESAK - Dini Ulya Fitriani (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
The development of religiosity in early childhood, especially children aged 5-6 years, is very important for inculcating religious awareness from an early age. In this millennial era, children are very easily exposed to negative influences from several sources such as from society, gadgets, and the environment, which greatly affects religiosity in children. This study aims to determine how the process of developing the religiosity of children aged 5-6 years, the obstacles and solutions in the process of developing children's religiosity at the Al-Qur'an Education Park (TPQ) Hadiqotul Afham, Peresak Hamlet, Sepakek Village, Pringgarata District, Central Lombok Regency.The type of research used is qualitative research and uses a descriptive approach. The results of this study indicate that efforts to develop children's religiosity are by instilling religious knowledge, in the form of developing religiosity in the fields of Aqidah, Morals and Shari'ah. The obstacles faced in the form of: educators/teachers, infrastructure, community. To overcome these obstacles, the owner of the TPQ/Teacher institution held outreach to the people of Peresak Hamlet, related to the importance of developing children's religiosity in TPQ. Conclusion Since the child entered the Hadiqotul Afham Al-Qur'an Education Park (TPQ) Peresak Hamlet, the development of children's religiosity has increased both in terms of Aqidah, Morals, and Sharia.